The Boundaries of the Unconscious - Rodrigo Barros Gewehr (Critical Hermeneutics)
The psyché-soma difference (Bartoš 2006) is one of the structuring themes not only of Western thought but also of modern psychology, which inherits this debate from the philosophical tradition and the religious tradition. Through a journey with early texts by Henri Bergson, including the psychology and metaphysics classes he taught at the Lycée de Clermont-Ferrand in 1887-1888, as well as the psychophysical parallelism of 1901, we address the difficulties pointed out in the monist position and its reverberations in contemporary psychology, which are commanded by neuroscience and cognitive psychology. We intend to highlight the impasses of the monist position that continue to be re-edited. In fact, despite countless technological advances concerning the issue of the nature of this duality, the debates seem to have stopped at the assertions that Bergson already denounced at the end of the 19th century and beginning of the 20th century, which denotes the strong presence of ontological options that largely overlap with the empirical inspiration of modern science. What are the determining lines in the resistance to this debate? Why do advances in research technologies not correspond to advances in the argument about this duality? Are there practical consequences for the reading of reality when adopting the monist principle, which remains sovereign in Western thought albeit unproven? These questions will guide the reflection we begin in this work.